Friesland - Thijsse, Jac. P. (Jacobus Pieter), 1865-1945; Koning, Edzard Willem, 1869-1954; Voerman, Jan, 1890-1976; Wenckebach, L. W. R. (Ludwig Willem Reymert), 1860-1937 (Salt Lake City, UT : Project Gutenberg, 2024)
"Friesland" by Jac. P. Thijsse is a travelogue written in the early 20th century. The narrative focuses on the author s explorations of Friesland, a picturesque region in the Netherlands, capturing its landscapes, history, and natural beauty. The work is likely to appeal to readers interested in travel literature, nature observations, and local history, as it vividly details the unique charm and character of the area. At the start of the narrative, Thijsse expresses excitement about traveling through Friesland, a land rich with diverse beauty both in its waterways and landscapes. As the author recounts his journey, he describes the surroundings with vivid imagery, detailing the transition from familiar Dutch environments to the distinct features of Friesland. He reflects on the historical significance of the paths he traverses and muses about the connections between place names and ancient forests, hinting at the region's deep-rooted heritage. The initial chapters feature encounters with charming villages, lush farmlands, and the tranquility of nature, inviting readers to experience Friesland through his eyes. (This is an automatically generated summary.)
Release date is 2024-10-13
The Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Fryslân (Netherlands) -- Description and travel -- Juvenile literature; Advertising cards -- Netherlands; Koninklijke Verkade (Firm) -- Collectibles